Environmental and Social Disclosure in Australian Mining Industry - lu, xiaolu (2006)
The purpose of this paper is to examine how Australian mining industry performs in environmental and social disclosure. There is growing public consensus that corporations should take responsibility for their environmental and social activities, which have already produced a massive amount of social problems such as wastes or pollutions. In response to the increasing public demand, environmental and social disclosure has developed rapidly during last decades. The paper tries to attribute to the literature by examining how the Australian mining industry performs in environmental and social disclosure. Content analysis will be conducted through twenty largest Australian mining companies and the result will be compared with previous literature when is appropriate. This analysis confirms the leading position mining industry has obtained over other industries. The relative emphasis placed on different disclosure categories will be discussed and the size relationship will be examined. The result suggests that larger mining companies are now tending to make the environmental and social disclosure in a separated report rather than annual report, which makes it necessary to extend the scope of disclosure analysis in the future.